Effects of the peripherally acting μ-opioid receptor antagonist methylnaltrexone on acute pancreatitis severity: study protocol for a multicentre double-blind randomised placebo-controlled interventional trial, the PAMORA-AP trial - Cecilie Siggaard Knoph; Mathias Ellgaard Cook; Camilla Ann Fjelsted; Srdan Novovic; Michael Bau Mortensen; Liv Bjerre Juul Nielsen; Mark Berner Hansen; Jens Brøndum Frøkjær; Søren Schou Olesen; Asbjørn Mohr Drewes (Trials, 2021)
Abstract Background Moderate to severe acute pancreatitis (AP) is associated with a high rate of complications and increased mortality, yet no targeted pharmacologic treatment currently exists. As pain is a dominant symptom in AP, patients are exposed to excess levels of both endo- and exogenous opioids, which may have harmful effects on the course of AP. This trial investigates the effects of the peripherally acting μ-opioid receptor antagonist (PAMORA) methylnaltrexone on disease severity and clinical outcomes in patients with moderate to severe AP. Methods PAMORA-AP is a multicentre, investigator-initiated, double-blind, randomised, placebo-controlled, interventional trial, which will be conducted at four referral centres for acute pancreatitis in Denmark. Ninety patients with early-onset AP (pain onset within 48 h) as well as predicted moderate to severe disease (two or more systemic inflammatory response syndrome criteria upon admission) will be prospectively included. Subsequently, participants will be randomised (1:1) to intravenous treatment with either methylnaltrexone or matching placebo (Ringer’s lactate) during 5 days of admission. The primary endpoint will be the group difference in disease severity as defined and measured by the Pancreatitis Activity Scoring System (PASS) score 48 h after randomisation. Secondary endpoints include daily PASS scores; disease severity according to the Atlanta classification; quantification of need for analgesics, nutritional support, intravenous fluid resuscitation and antibiotics; duration of hospital admissions, readmission rates and mortality. Pain intensity and gut function will be self-reported using validated questionnaires. Exploratory endpoints include circulating levels of pro-and anti-inflammatory markers, polyethylene glycol recovery from the urine, circulating levels of blood markers of intestinal permeability, the prevalence of pancreatic complications on computed tomography (CT) scans, and colon transit time assessed using a CT-based radiopaque marker method. Discussion This trial aims to evaluate the PAMORA methylnaltrexone as a novel targeted pharmacotherapy in patients with moderate to severe AP with the potential benefit of improved patient outcomes. Trial registration ClinicalTrials.gov NCT04743570 . Registered on 28 January 2021. EudraCT 2020-002313-18.